Respuesta :

Answer:

Solution: x = -2; y = 3 or (-2, 3)

Step-by-step explanation:

Equation 1:  y = -5x - 7  

Equation 2: -4x - 3y = -1

Substitute the value of y in Equation 1 into the Equation 2:

-4x - 3(-5x - 7)  = -1

-4x +15x + 21 = -1

Combine like terms:

11x + 21 =  - 1

Subtract 21 from both sides:

11x + 21 - 21 =  - 1 - 21

11x = -22

Divide both sides by 11 to solve for x:

11x/11 = -22/11

x = -2

Now that we have the value for x, substitute x = 2 into Equation 2 to solve for y:

-4x - 3y = -1

-4(-2) - 3y = -1

8 - 3y = -1

Subtract 8 from both sides:

8 - 8 - 3y = -1 - 8

-3y = -9

Divide both sides by -3 to solve for y:

-3y/-3 = -9/-3

y = 3

Therefore, the solution to the given systems of linear equations is:

x = -2; y = 3 or (-2, 3)

Please mark my answers as the Brainliest if you find this helpful :)